Desenvolvimento de gerador de campo magnético alternado para avaliação in vitro de hipertermia em cultura celular - Pederiva, Mansueto Bartelega (2014)
The human body is made of millions of cells that reproduce through cell division and that, under normal conditions, is controlled, but in some situations the cells lose the capacity to control their own growth, forming what is known as a malignant tumor or cancer. There are several ways to treat cancer such as drugs, surgery, radiotherapy among others. Lately emerged a technique based on magnetic nanoparticles used in association to the hyperthermia. The new technique consists in insert magnetic nanoparticles in the diseased tissue and cause the destruction of cancer cells through its heating above 41 °C using an alternating magnetic field generators. Nowadays, only imported equipment is in the market at a high cost and made by complex electronic circuits. In order to nationalize and decrease the cost of this technology, the aim of this work was the construction of an alternating magnetic field generator for evaluation of hyperthermia in vitro in cell culture. It was necessary to evaluate how similar imported equipment works. As a started point model, a national industrial equipment used for melting metals was used. The circuits were built and modified for heating magnetic nanoparticles. The prototype was built and compared with the imported equipment used to heat magnetic nanoparticles. It was observed that the prototype heats the magnetite particles even in micrometric or nanometric sizes above 41°C. It was also observed a relation between the intensity of the alternating magnetic field and its frequency with the amount of water present as dispersion media for magnetic particles. The prototype was able to heat magnetic nanoparticles achieving a value of heating satisfactory to hyperthermia treatment. Thus, the feasibility to construct a pilot as national alternating magnetic field generator was proven.